Genomic Targets in Inflammation and in Allergic Reactions: A Patientoriented Approach - Saito, H. (Anti-Inflammatory & Anti-Allergy Agents in Medicinal Chemistry, 2006)
Along with advances in the genome sequencing and microarray technologies, many attempts have been made to understand the human diseases systemically. Here, literatures regarding genomic studies on allergic diseases are reviewed, especially by focusing on microarray-based transcriptome studies. In earlier patient-oriented transcriptome studies related to allergy and inflammation, only a few projects seem to be successful considering the amounts of time, labor and research grants. Most frequently observed among the problems in such studies are contamination by a different cell type having a certain highly expressed transcript that may cause a virtual increase in the transcript number in the whole population even where the major cell type lacks it. The successful transcriptome studies are therefore commonly obtained by using cell lines, highly purified cells or gene-targeting cell lines for microarray analysis as the first screening. A cell-type specific transcriptome database is also useful for determining whether an increase of a certain transcript in inflammatory tissues reflects an increase in its expression level or an increase in the number of inflammatory cells. Nevertheless, high quality RNA samples are necessary for obtaining reproducible results in the present transcriptome assays using clinical samples. In this context, analysis for genome-wide chromatin structure will be useful to understand the transcriptome more precisely. Considering the rapid development of microarray and data mining technologies, it is well expected.
Keywords: mast cells